Soil organic carbon sequestration in croplands can make remarkable contributions to China's carbon neutrality. (1st January 2023) - Zuo, Wengang; Gu, Binxian; Zou, Xiaowei; Peng, Kun; Shan, Yuli; Yi, Siqiang; Shan, Yuhua; Gu, Chuanhui; Bai, Yanchao
Abstract: The vast cropland in China is an important carbon pool with substantial carbon sequestration potential. Here, this study estimated the soil organic carbon stock in China's croplands based on a comprehensive investigation of 7.5 million soil samples from 2209 counties. We show that China's croplands (0–20 cm) store 4.53–4.98 Pg organic carbon in total. The soil organic carbon stock increased from 29.13–34.54 to 33.51–36.90 Mg C ha −1 during 1980–2010, with an annual average increase rate of 113.33 kg C ha −1 yr −1 . The increase in soil organic carbon stock was mainly driven by the increasing inputs of crop residue and livestock manure. Furthermore, we designed four scenarios with different crop residue, livestock manure, and nitrogen fertilizer inputs to assess the soil organic carbon sequestration potential in China's croplands. The results show that the soil organic carbon storage is projected to reach 6.98–7.89 Pg by 2060, representing 6.1%–13.3% of the annual negative carbon emissions required by 2060 China's carbon neutrality target. We also proposed targeted strategies to further increase the soil organic carbon stock of cropland in different regions by considering characteristics such as soil properties and agricultural management practices.